I. PRAYERS OF FEMALE PROTAGONISTS IN GIUSEPPE VERDI’S OPERAS FENENA’S PRAYER: OH, DISCHIUSO È IL FIRMAMENTO - Adél FEKETE (Studia Universitatis Babeş-Bolyai. Musica)
With this analysis the author begins a journey of presenting the prayers of female protagonists from Giuseppe Verdi’s operas, a lesser-known topic within the vast bibliography dedicated to the oeuvre of the great Italian Maestro. Fenena’s Prayer from Nabucco opens the author’s series of analyses of preghiere written for the solo female voice found in ten of the composer’s works, covering all three of Verdi’s creative periods. Further analyses published in this series will shed light upon well-known examples of preghiere – like the famous prayers of Leonora from La Forza del Destino –, as well as forgotten pages of Verdi’s works which at times present surprising elements, such as the very modern prayer of Giselda from I Lombardi alla prima crociata. Other such segments will be arias which bear bel canto influences (preghiere from Giovanna d'Arco and Stiffelio), but also ones illustrating the language transformation of the female prayer in more mature operatic works, such as Aida and Otello.